Dynamics of Sporulation of Caprine Eimerian Species under Variable Temperature and Humidity in Semi-arid Region of India - Verma, Rupesh; Sharma, Dinesh Kumar; Gururaj, K.; Paul, Souvik (International Journal of Livestock Research, 2021)
The present investigation was carried out to understand the sporulation dynamics of prevalent nine Eimeria oocysts viz. E. alijevi, E. apsheronica, E. arloingi, E. caprina, E. christenseni, E. hirci, E. jolchijevi, E. ninakohlyakimovae and E. caprovina seen at Central Institute for Research on Goats, Makhdoom, Mathura was studied. Fresh faeces samples were collected from three diﬀerent goat breed farms (Jamunapari, Jakhrana and Barbari) and examined for the presence of Eimerian oocysts. Eimerian oocysts were collected and kept under ordinary laboratory sporulation conditions in 2.5% potassium dichromate at different ambient temperature and humidity for sporulation. The proportion of sporulated oocysts was determined microscopically every 8-12 h. At the average temperature and relative humidity of 11.8˚C & 82.19, 16.9˚C & 64.73 and 30.5˚C & 48.33, the sporulation time was observed as 3-6 days, 2-5 days and 1-4 days, respectively. But 50% of oocysts completed sporulation at average temperature and humidity of 32.42 ˚C & 22.88, respectively.